Effectiveness of dentin pre-treatment on bond strength of two self-adhesive resin cements compared to an etch-and-rinse system: an in vitro study - Milad Hammal; Zdeněk Chlup; Tomáš Ingr; Ján Staněk; Radek Mounajjed (PeerJ, 2021)
Statement of problem It has been shown that selective etching improves the bond strength of some self-adhesive resin cements to enamel. The same has yet to be determined with dentin pre-treatment. Purpose To evaluate the tensile bond strength of two self-adhesive resin cements after two dentin surface pre-treatments, and also to analyze the cement/dentin interface. Material and Methods One hundred and twelve human third molars were extracted. The teeth were distributed into seven groups (n = 16). Maxcem Elite Chroma (MAX) (Kerr, Scafati, Italy) and Relyx U200 (RLX) (3M ESPE, Neuss, Germany) were used without pre-treatment or with two dentin pre-treatments (polyacrylic acid or phosphoric acid). A conventional etch-and-rinse (EAR) luting cement, NX3 Nexus (NX3) (Kerr, Scafati, Italy), was used as an external control group. Before testing, all specimens were stored in distilled water for 24 hours. Three specimens from each group were prepared for scanning electron microscopy observation (SEM). A tensile bond strength test (TBS) was performed for the remaining samples. The data were statistically analyzed using the Kruskal–Wallis test and Pairwise comparisons using the Wilcoxon rank sum test. Results MAX without pre-treatment and with phosphoric acid etching attained statistically similar bond strengths to NX3 (P > 0.05). There was a statistical difference (P = 0.00488) between RLX without pre-treatment (5.62 MPa) and NX3 (10.88 MPa). Phosphoric acid pre-treatment increases the bond strength values of RLX to a strength that is comparable to NX3 (P > 0.05). The lowest tensile bond strength (TBS) was attained after the application of polyacrylic acid with MAX (1.98 MPa). No statistical differences were found between the RLX bond strength values after polyacrylic acid treatment and RLX without pre-treatment or NX3 (P > 0.05). SEM observations disclosed an enhanced potential of the self-adhesive cements to infiltrate into dentin tubules and form resin tags when applied after phosphoric acid pre-treatment. The failure mode was dominantly adhesive. Conclusions On dentin, the self-adhesive resin cement MAX might be an effective alternative to conventional resin cement. Etching the dentin with phosphoric acid does not have a negative effect on the bond strength of MAX to dentin. On the other hand, phosphoric acid improved the bond strength of RLX when compared to EAR cement.